Análisis del abordaje de la literacidad digital en las prácticas docentes en pospandemia. Un estudio de caso (2022)
In this research monograph, it presents as a fundamental characteristic, recognizing the digital literacy strategies developed before, during and after the pandemic and that are still frequently maintained today based on the experience of teachers and students.